Healthcare‐associated, community‐acquired and hospital‐acquired bacteraemic urinary tract infections in hospitalized patients: a prospective multicentre cohort study in the era of antimicrobial resistance. (22nd December 2012) - Horcajada, J. P.; Shaw, E.; Padilla, B.; Pintado, V.; Calbo, E.; Benito, N.; Gamallo, R.; Gozalo, M.; Rodríguez‐Baño, J.; ,; ,; ,; et al.
Abstract The clinical and microbiological characteristics of community‐onset healthcare‐associated (HCA) bacteraemia of urinary source are not well defined. We conducted a prospective cohort study at eight tertiary‐care hospitals in Spain, from October 2010 to June 2011. All consecutive adult patients hospitalized with bacteraemic urinary tract infection (BUTI) were included. HCA‐BUTI episodes were compared with community‐acquired (CA) and hospital‐acquired (HA) BUTI. A logistic regression analysis was performed to identify 30‐day mortality risk factors. We included 667 episodes of BUTI (246 HCA, 279 CA and 142 HA). Differences between HCA‐BUTI and CA‐BUTI were female gender (40% vs 69%, p <0.001), McCabe score II–III (48% vs 14%, p <0.001), Pitt score ≥2 (40% vs 31%, p 0.03), isolation of extended spectrum β‐lactamase‐producing Enterobacteriaciae (13% vs 5%, p <0.001), median hospital stay (9 vs 7 days, p 0.03), inappropriate empirical antimicrobial therapy (21% vs 13%, p 0.02) and mortality (11.4% vs 3.9%, p 0.001). Pseudomonas aeruginosa was more frequently isolated in HA‐BUTI (16%) than in HCA‐BUTI (4%, p <0.001). Independent factors for mortality were age (OR 1.04; 95% CI 1.01–1.07), McCabe score II–III (OR 3.2; 95% CI 1.8–5.5), Pitt score ≥2 (OR 3.2 (1.8–5.5) and HA‐BUTI OR 3.4 (1.2–9.0)). Patients with HCA‐BUTI are a specific group with significant clinical and microbiological differences from patients with CA‐BUTI, and some similarities with patients with HA‐BUTI. Mortality was associated with patient condition, the severity of infection and hospital acquisition.